The Impact of Economic Migration on Childrens Cognitive Development: Evidence from the Mexican Family Life Survey - Elizabeth Powers (Inter-American Development Bank (IDB), 2011)
This paper uses data from the Mexican Family Life Survey to estimate the impact of a household members migration to the United States on the cognitive development of children remaining in Mexico. While there is no developmental effect of a childs sibling migrating to the United States, there is an adverse effect when another household membertypically the childs parentmigrates. This is particularly true for pre-school to early-school-age children with older siblings, for whom the effect of parental migration is comparable to speaking an indigenous language at home or having a mother with very low educational attainment. Additionally, household-member migration to the United States affects how children spend their time in ways that may influence and/or be influenced by cognitive development.
Keywords: I12; I38; J11; J61; O15; 330